2023
DOI: 10.3389/frph.2023.1100029
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis: a review of approaches to treatment and prevention

Abstract: Bacterial vaginosis (BV) is a common cause of vaginitis worldwide and is associated with serious reproductive health outcomes, including increased risk of preterm birth, sexually transmitted infections, and pelvic inflammatory disease. The current and only FDA-approved treatment regimens for BV are antibiotics, such as metronidazole and clindamycin. Antibiotics provide a short-term cure for bacterial vaginosis; however, fail to provide a consistent long-term cure for many women. Fifty to eighty percent of wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 147 publications
0
14
0
Order By: Relevance
“…Previous research has brought attention to the limited predictive value of the Bishop score in determining the success of induction and the potential for adverse outcomes in multiparous women. Additionally, these studies have suggested that regardless of their initial Bishop scores, multiparous women can undergo induction safely and have successful outcomes [32]. Our research successfully gathered comprehensive data on bacterial vaginosis (BV) in women who underwent induced labour during the third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has brought attention to the limited predictive value of the Bishop score in determining the success of induction and the potential for adverse outcomes in multiparous women. Additionally, these studies have suggested that regardless of their initial Bishop scores, multiparous women can undergo induction safely and have successful outcomes [32]. Our research successfully gathered comprehensive data on bacterial vaginosis (BV) in women who underwent induced labour during the third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 94%
“…Given the high frequency of BV recurrence, alternatives to antibiotics are currently being studied for BV treatment, including interventions targeting vaginal pH, biofilms and restoration of a Lactobacillus dominant vaginal microbiome. Lower, acidic vaginal pH limits growth of BV‐associated anaerobes, therefore, lactic acid‐based interventions have been investigated though thus far they have not been shown to reliably treat BV in small studies compared to standard antibiotic treatment 6,53 . Two biofilm disruptors have shown promising results in small studies though neither is currently available in the US.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in women living with HIV, vaginal dysbiosis and mucosal inflammation have been linked to genital HIV shedding, which may increase HIV transmission risk 4,5 . Effective treatments for BV are lacking, 6 therefore, understanding factors that influence BV risk is critical 7 …”
Section: Introductionmentioning
confidence: 99%
“…The vaginal microbiome, in a physiologically normative context, manifests as an intricate and equilibrium-maintained ecological construct. Lactobacillus species predominantly characterize the healthy vaginal microbiome and are recognized for their role in safeguarding the vaginal ecosystem via the secretion of antimicrobial agents, including lactic acid, hydrogen peroxide, and bacteriocin-like compounds [14]. The production of lactic acid contributes to the acidic vaginal milieu (pH 3.5-4.5), facilitating the proliferation of Lactobacillus and inhibiting the colonization of pathogenic microorganisms [15].…”
Section: Introductionmentioning
confidence: 99%